LONGEVITY SELECTION AND LIABILITIES IN PUBLIC SECTOR PENSION FUNDS. Issue 1 (10th July 2013) - Fong, Joelle H.; Piggott, John; Sherris, Michael
Abstract This article assesses the cost and risk faced by public sector, defined benefit plan providers arising from uncertain mortality, including longevity selection, mortality improvements, and unexpected systematic shocks. Using longitudinal microdata on Australian pensioners, we quantify the extent of longevity selection at both aggregate and scheme level. We also show that as the age‐membership structure in a pension scheme matures, scheme‐specific longevity selection risk and systematic shocks become quantitatively more important and have larger consequences for plan liabilities than aggregate selection risk or the impact of mortality improvements.